Can sodium bicarbonate supplementation improve combat sports performance? A systematic review and meta-analysis - Silva Miranda, W. A.; Brabec Mota Barreto, L.; Miarka, B.; Espinoza Salinas, A.; Sorbazo Soto, D. A.; Aedo Muñoz, E. A.; Brito, C. J. (Current Nutrition Reports, 2022)
Purpose of Review: To verify the effects of sodium bicarbonate (NaHCO3) supplementation on biochemical and physical measurements of combat sports athletes. Recent Findings: A systematic review: of articles indexed in three databases (PubMed, CAPES journal, and Google Scholar) was carried out until October 2020, using descriptors related to NaHCO3 supplementation in combat sports. First, 38 articles were identified. Next, eight articles were selected through the inclusion and exclusion criteria. The methodological quality of the articles was assessed using the Physiotherapy Evidence Database (PEDro) scale (8 and 9 points). Blood lactate, rating of perceived exertion, Special Judo Fitness Test, Dummy throw, and mean and peak powers for Wingate were evaluated. Random effects meta-analysis was used, the effect size was adjusted by corrected Hedges` g, and the heterogeneity is explored by I2. The results were obtained through weighted average and 95% CI, and the significance limit was set as p < 0.05. Summary: NaHCO3 supplementation had a significant effect on increasing blood lactate (p = 0.006) of the athletes studied. However, the performance measures (rating of perceived exertion, power, and specific performance) did not show a significant difference (p < 0.05). In conclusion, NaHCO3 supplementation causes a significant increase in blood lactate, indicating an ergogenic effect on buffer, which can delay the onset of fatigue and contribute to the performance of combat sports athletes. New experimental studies need to be published that assess the effect of acute and chronic NaHCO3 supplementation in specific combat sports tests and in women.